An overview of the use of plants, polymers and nanoparticles as antibacterial materials - Milad Sheydaei; Shabnam Shahbazi-Ganjgah; Ebrahim Alinia-Ahandani; Melika Sheidaie; Milad Edraki (Chemical Review and Letters, 2022)
The expansion of industry, climate change, deforestation, and pollution of oceans, and exponential increase in the multidrug-resistant bacteria, humans are more to danger than ever before. In recent years, humans have been affected more than ever by bacterial and fungal infections and even mosquito-related diseases such as lymphatic filariasis, malaria, and cellulitis. For example, Candida albicans and Aspergillus fumigatus can cause invasive fungal infections in any organ of humans, and their resistance to antibiotics is increasing. For a long period of time, plant components have been used for curing the various ailments. Herbs were the basis of medicine in the past and also are extensively used in some countries such as China and India. The study of antimicrobial effects of plants is increasing continuously, which is due to the presence of diverse levels of their bioactive compounds. Humans are so interested in using natural antibacterial compounds like plant extracts and spices because they have their own characteristic flavor. Plants are useful for supporting human health and some parts of the plant (flowers, leaves, stems, and roots) have medicinal activities such as analgesics, antispasmodics, antimicrobials. With recent advances, in addition to plants, polymers and nanoparticles have come to the help of medical cures. Polymers and nanoparticles due to their unique properties, can be used in a variety of fields such as prosthesis, antibacterial and antifungal surfaces, drug carrier, gene delivery, cancer diagnosis, colorimetric detection of cancer cells, and cancer imaging. In this study, researches on plants, polymers, and nanoparticles antibacterial are reviewed.